2011
DOI: 10.1037/a0022423
|View full text |Cite
|
Sign up to set email alerts
|

Implications of attachment theory and research for the assessment and treatment of eating disorders.

Abstract: In this paper, we review the research literature on attachment and eating disorders and suggest a framework for assessing and treating attachment functioning in patients with an eating disorder. Treatment outcomes for individuals with eating disorders tend to be moderate. Those with attachment-associated insecurities are likely to be the least to benefit from current symptom-focused therapies. We describe the common attachment categories (secure, avoidant, anxious), and then describe domains of attachment func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
1
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 92 publications
1
101
1
12
Order By: Relevance
“…Family structure and communication are also central to the concept of the psychosomatic (e.g. anorectic) family (Minuchin, Rosman, & Baker, 2009) and the person-al traits which are influenced by these family characteristics are also crucial for eating disorder patients (Tasca, Ritchie, & Balfour, 2011;Túry & Pászthy, 2008).…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Family structure and communication are also central to the concept of the psychosomatic (e.g. anorectic) family (Minuchin, Rosman, & Baker, 2009) and the person-al traits which are influenced by these family characteristics are also crucial for eating disorder patients (Tasca, Ritchie, & Balfour, 2011;Túry & Pászthy, 2008).…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
“…As disturbances of personality and family functioning are among the most important predisposing, precipitating and maintaining factors for eating disorders, (Túry & Pászthy, 2008), in eating disorders attachment could be viewed as a system mediating between interpersonal and intrapersonal experiences. Attachment functioning may play a particularly important role in cases where there are comorbid psychopathologies, emotion-processing deficits, personality disorders and insecure attachment, as these patients respond less well to simple, symptom-focused therapies (Myers et al, 2006;Tasca et al, 2011). In spite of these highly important contributory mechanisms of attachment to eating disorder symptoms, mainstream treatment models emphasize the biological, cultural, or most often cognitive-behavioral traits of these disorders, without taking into account dynamic concepts or attachment issues .…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wei and colleagues (15) determine that affect regulation perform as mediator between attachment dimensions and negative mood in a sample of college students. In another research declared that emotion focused coping mediate in the relationship between attachment anxiety and body image disturbances, depression and problem eating, hence can assert that affect regulation strategies has role in mediating the relationship between attachment dimensions and both depressive and eating disorder (ED) symptoms (25,26). Hilbert and Tuschen-Caffier (27) also found that binge eating was preceded by difficulty in regulating affect in females with Bulimia nervosa.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the AAI coding system considers the Coherence of Mind and the Coherence of Transcript as the most accurate indicator of the state of mind with respect to attachment [39]. The poor CoM which has been found in AN patients suggests difficulty in creating a narrative process on psychological development, self-awareness and incoherencies on the report of their own experiences [40,41]. CoM and CoT positively correlated with the volume of GM in a network of brain areas comprising the temporal poles, both amygdalae, the midbrain, the thalamus and the anterior and middle sections of cingulate cortex [27,30].…”
mentioning
confidence: 99%